Efficacy of a multifactorial strategy for bowel preparation in diabetic patients undergoing colonoscopy: a randomized trial - Alvarez-Gonzalez, Marco Antonio; Flores-Le Roux, Juana A.; Seoane, Agustin; Pedro-Botet, Juan; Carot, Laura; Fernandez-Clotet, Agnés; Raga, Agnés; Pantaleon, Miguel A.; Barranco, Luis; Bory, Felipe; Lorenzo-Zuñiga, Vicente (Endoscopy, 2016)
Background and study aims: Previous studies have reported that diabetes mellitus is an independent risk factor for inadequate bowel preparation. Current guidelines do not recommend a specific preparation for this patient population. The aims of this study were to assess the efficacy, safety, and tolerability of an adapted preparation protocol for colon cleansing in patients with type 2 diabetes mellitus. Patients and methods: This randomized, single-blind, parallel group, superiority trial compared a conventional bowel preparation protocol (CBP) with a diabetes-specific preparation protocol (DSP). The CBP included a low-fiber diet for 3 days followed by a clear liquid diet for 24 hours before colonoscopy. The DSP included a multifactorial strategy combining an educational intervention, a low-fiber diet, and adjustment of blood glucose-lowering agents. All patients received 4 L of a polyethylene glycol solution in a split-dose regimen. The endoscopists were blinded to the preparation protocol. The primary outcome measure was inadequate bowel preparation according to the Boston Bowel Preparation Scale. Secondary outcome measures included hypoglycemic events, tolerability, and acceptability. Results: A total of 150 patients were included in the study (74 CBP and 76 DSP). Both groups were comparable in terms of baseline characteristics. Inadequate bowel cleansing was more frequent following CBP than DSP (20 % vs. 7 %, P = 0.014; risk ratio 3.1, 95 % confidence interval 1.2 – 8). Only CBP and performance status were independently associated with inadequate bowel preparation. Both preparations were equally tolerated and accepted by patients, and side-effects were similar between the groups. Conclusions: A multifactorial strategy for bowel preparation in patients with diabetes undergoing colonoscopy showed a threefold reduction in the rate of inadequate bowel preparation, with no differences in safety and tolerability compared with conventional preparation. Trial registration: ClinicalTrials.gov (NCT02300779).